Digital transformation - opportunities and challenges in heathcare: opportunities and challenges in healthcare - Saranto, Kaija (Revista Fontes Documentais, 2024)
Digital transformation is defined as using digital technologies to transform businesses and services and replace traditional processes with digital technologies to improve, advance, or streamline working methods. The comprehensive transformation has been ongoing for decades. Still, using digital technologies in health care was no longer an option during the Pandemic when new ways of providing care and services were needed. The Pandemic touched patients and professionals and made the leaders focus more on security, privacy, and technolog.